Pre-operative therapeutic eyelid hygiene in the prevention of complications following excimer laser vision correction - V. V. Kurenkov; A. V. Zhemchugova; E. G. Polunina; S. I. Abramov; A. A. Kozhuchov (Oftalʹmologiâ, 2014)
Purpose: to assess the effectiveness of pre-operative therapeutic eyelid hygiene in the prevention and treatment of dry eye and meibomian glands dysfunction following excimer laser vision surgery.Methods: In enrolled 144 patients (288 eyes), ocular surface and meibomian glands functions were evaluated before and following refractive surgery (LASIK and REIK). In pre- and post-operative period, standard ophthalmological studies were performed, including best-corrected visual acuity determination, biomicroscopy, Schirmer’s test and Norn’s test (tear break-up time). In pre-operative pe- riod, ocular surface microbial profile was assessed. Subjective symptoms of impaired tear production were revealed via questioning. In study group (70 patients, 140 eyes), therapeutic eyelid hygiene using Blefarogel 1 or Blefarogel 2 (Ltd. Heltec-Medica, Moscow, Russia) was prescribed one week before surgery. In control group, no therapeutic eyelid hygiene was prescribed. All patients were received antibacterial treatment including Vigamox (Alcon, Fort Worth, tX). In both groups, Natural tears and Systane Ultra (Alcon) were used as tear replacement therapy.Results: Complex treatment, including therapeutic eyelid hygiene in study group, significantly improved tear film and ocular sur- face health as well as meibomian glands functions. Inflammatory complications rate was estimated as 5.7% in study group and 10.6% in control group.Conclusion: therapeutic eyelid hygiene is highly effective in the prophylaxis and treatment of post-operative complications duу to ocular surface pathology and meibomian glands dysfunction. the procedure is safe and can be recommended as a part of complex preventive treatment before excimer laser vision correction.